Caracterização física dos resíduos sólidos domiciliares em diferentes formas de habitação - Salsa, Noelle Santos (2013)
As a result of the development of cities, one of the challenges of public management is the management of municipal solid waste. The publication of the Brazilian Solid Waste Policy (Law No. 12.305/2010), on the principle of shared responsibility, has established specific duties to the Government, companies and the citizen with regard to management steps. Therefore, the present study aimed to show the importance of a proper household solid waste management in condominiums, because when more families are concentrated more increases the amount of waste generated and the complexity of its collection and management. Thus, it was possible to understand the dynamics of household solid waste generation in different forms of housing and in cities with different economic vocations. In the city of Londrina PR, it was analyzed a vertical and a horizontal condominium, each one in a different region of the municipality and in Balneário Camboriú-SC was analyzed a vertical condominium, which can be compared with the other condominiums. The physical characteristics studied were: per capita generation, specific mass and gravimetric composition. In addition, it was made analysis of how the condos manage their waste to suggest improvements in the process. The results showed that there is a variation in the gravimetric composition of the waste in different forms of housing and location of cities. The percentage of organic waste and recyclable waste ranged in all condos, due to the number of inhabitants, educational level, climatic conditions, customs of the population and as the form of waste collection. Per capita generation was different in all condos, confirming the hypothesis that there is difference of per capita generation according to the type of housing and according to their location. The specific masses of recyclable materials showed major differences between all condos, highlighting the importance of the determination of this parameter for the purpose of conditioning and shelters end projection. As improvements to waste management in all condos it is necessary environmental education actions to sensitize the importance of waste selective collection.